2020
DOI: 10.21203/rs.3.rs-19308/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glioma patients in outpatient care - Optimization of psychosocial care in neuro-oncological patients (GLIOPT): Protocol for a cluster randomized controlled trial.

Abstract: Background: Patients with high-grade gliomas (HGG) often suffer from high distress and require psychosocial support. However, due to neurological and neurocognitive deficits, adequate assessment of distress and support needs remains a challenging unmet clinical need. The objective of the present study is to investigate whether a systematic implementation of signaling questions into the routine outpatient consultation will be helpful to bridge this gap.Methods and design:This is a multicenter cluster randomized… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Studies have shown [14][15][16] that taking different psychological interventions before surgery to strengthen the cognitive function of patients has a significant effect on eliminating bad emotions. Studies have also shown [17,18] that an effective care model can significantly reduce the incidence of adverse reactions in cancer chemotherapy patients and improve the tolerance and treatment confidence of patients with adverse reactions to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown [14][15][16] that taking different psychological interventions before surgery to strengthen the cognitive function of patients has a significant effect on eliminating bad emotions. Studies have also shown [17,18] that an effective care model can significantly reduce the incidence of adverse reactions in cancer chemotherapy patients and improve the tolerance and treatment confidence of patients with adverse reactions to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%